2022
DOI: 10.1186/s12931-022-02000-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of air pollution exposure with exercise-induced oxygen desaturation in COPD

Abstract: Background There is a link between exposure to air pollution and the increased prevalence of chronic obstructive pulmonary disease (COPD) and declining pulmonary function, but the association with O2 desaturation during exercise in COPD patients with emphysema is unclear. Our aims were to estimate the prevalence of O2 desaturation during exercise in patients with COPD, and determine the association of exposure to air pollution with exercise-induced desaturation (EID), the degree of emphysema, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…According to the World Health Organization, environmental factors have a role in 35% of infectious disorders involving the lower respiratory tract, and SARS-CoV-2 infections were no exception [42]. Some studies found that there was a relationship between exposure to air pollutants (PM 2.5 , PM 10 , NO 2 , O 3 , SO 2 ) and the increased prevalence of chronic obstructive pulmonary disease (COPD) [43] and the weakening of pulmonary function [44]. A study in the United States found that an increase of 1 µg/m 3 in PM 2.5 was associated with an 8% increase in the COVID-19 death rate (95% CI: 2-15%) [45].…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization, environmental factors have a role in 35% of infectious disorders involving the lower respiratory tract, and SARS-CoV-2 infections were no exception [42]. Some studies found that there was a relationship between exposure to air pollutants (PM 2.5 , PM 10 , NO 2 , O 3 , SO 2 ) and the increased prevalence of chronic obstructive pulmonary disease (COPD) [43] and the weakening of pulmonary function [44]. A study in the United States found that an increase of 1 µg/m 3 in PM 2.5 was associated with an 8% increase in the COVID-19 death rate (95% CI: 2-15%) [45].…”
Section: Discussionmentioning
confidence: 99%
“…First, a spirometer (Vitalograph Spirotrac-5™, Vitalograph, MK18 1SW, Buckingham, UK) was utilized to measure the FEV 1 and FVC, and then to derive the FEV 1 /FVC ratio. The measurement procedures were documented in previous studies ( 16 , 17 ). Notably, all patients were instructed to stop using their bronchodilator, which was their regular medication, 1 day before the PFT.…”
Section: Methodsmentioning
confidence: 99%